Instantaneous fibrillation of egg white proteome with ionic liquid and macromolecular crowding - Pankaj Bharmoria (Nature Portfolio, 2020)
The applicability of protein fibrils as functional biomaterials is limited due to low scalability of production process, slow kinetics, and requirement of expensive purified proteins. Here, instantaneous production of protein fibrils from egg white proteome using cholinium tosylate as a fibrillation agent is shown, with the obtained fibrils displaying enhanced mechanical stiffness and cytocompatibility.